Management of obesity and cardiometabolic risk – role of phentermine/extended release topiramate - Sweeting AN (Dove Medical Press, 2014)
Arianne N Sweeting,1 Eddy Tabet,1 Ian D Caterson,1,2 Tania P Markovic1,2 1Department of Endocrinology, Royal Prince Alfred Hospital, Sydney, NSW, Australia; 2Boden Institute of Obesity, Nutrition, Exercise & Eating Disorders, University of Sydney, NSW, Australia Abstract: The US Food and Drug Administration (FDA) recently approved lorcaserin and the combination of phentermine and extended release topiramate (phentermine/topiramate ER) for the treatment of obesity in conjunction with a lifestyle intervention, expanding the therapeutic options for long-term obesity pharmacotherapy, which was previously limited to orlistat. Combination phentermine/topiramate ER is associated with greater weight loss compared to its constituent monotherapy, with a more favorable adverse effect profile. Phentermine/topiramate ER also appears to have beneficial effects on cardiometabolic risk, although longer-term cardiovascular safety data are required. While there are no head-to-head studies among the currently available obesity pharmacotherapy agents, phentermine/topiramate ER appears to have a superior weight loss profile. This review will discuss the epidemiology, natural history, and cardiometabolic risk associated with obesity, provide an overview on current obesity pharmacotherapy, and summarize the recent clinical efficacy and safety data underpinning the FDA's approval of both phentermine/topiramate ER and lorcaserin as pharmacotherapy for a long-term obesity intervention. Keywords: obesity, phentermine/topiramate extended release, safety and efficacy, review